Design of Portable Ultrasonic Ranger Based on MSP430F149 - MI Lan; JI Mei; MENG Lin-shan; GU Lin-zhu (Gong-kuang zidonghua, 2011)
According to ultrasonic ranging principle, a portable ultrasonic ranger based on MSP30F149 was designed. Design of hardware circuit of the ranger was introduced in details and main program flow of software of the ranger was given. The test result showed that the ranger has stable running and reliable performance, and measuring precision is 2 mm.